Shawshank redemption - C. Cuneen (Law Text Culture, 1995)
We all have an image of prison, some pictures of prisoners and imprisonment. My first experience of prison was as a teenager at my girlfriend's house opposite Long Bay goal. It must have been in the early 1970's, although I can't recall exactly when. It was Christmas time, possibly Christmas Day or Boxing Day. We were sitting on the front lawn drinking beer. I remember the burning and choking sensation of tear gas mixing with the hot summer air, and the family moving inside the house and closing the doors and windows. Her brother said there must be a riot at the goal. And he proceeded to tell stories about prisoners running down the street in front of the house, trying to take off their prison clothes as they ran.